Binary- and Three-Tiered Oral Epithelial Dysplasia Grading System and Malignant Transformation - Ellonen, Riikka; Kelppe, Jetta; Hagström, Jaana; Suominen, Auli; Willberg, Jaana; Rautava, Jaana; Laine, Hanna K (United States, 2025)
Objectives: Oral epithelial dysplasia (OED) can be graded histopathologically by using a binary- or three-tiered grading system. This study aimed to analyze and compare the prognostic value of the two systems in a large single-institute material.
Materials and methods: The study was a retrospective histopathological re-evaluation analysis of 612 OEDs over 29 years at the Institute of Dentistry, University of Turku, Turku, Finland. OED patients who later developed squamous cell carcinoma (OSCC) were identified from the Finnish Cancer Registry database.
Results: Altogether, the mean age of 612 OEDs patients was 59.9 years. The male:female ratio was 0.67. According to the original three-tiered diagnosis, 67.7% of the samples were mild dysplasia, 28.7% moderate dysplasia, and 3.6% severe dysplasia cases. With binary-tiered diagnosis, low-grade dysplasia 84.1% was more common than high-grade dysplasia 15.9%. The malignant transformation rate was 7.8%. Regarding oral SCC development, no difference was found between the grading systems in predicting the malignant progression (p = 0.060).
Conclusions: Both binary- and three-tiered grading systems of dysplasia classification had similar predictive value for malignant transformation.